Indonesia’s Trade Diplomacy Through FTA: Analysis on Actors, Processes, and Goals of Diplomacy - Killian, Pantri Muthriana Erza (UI Scholars Hub, 2020)
The purpose of this article is to examine the various FTAs that Indonesia has been involved in within the last 15 years by looking at the three core elements of trade diplomacy: actors, processes, and goals of FTAs. Based on these elements, this research finds that Indonesia’s FTA diplomacy tends to be dominated by foreign policy interests compared to economic ones, which can be observed through several elements. First, Indonesia’s FTA diplomacy is dominated by state actors and foreign policy players with little involvement from economic players and non-state actors. The numerous FTAs signed through ASEAN also reinforced this domination since ASEAN’s distribution of authority placed foreign policy players at a higher hierarchy than trade actors. Second, Indonesia’s FTA diplomacy tends to be inefficient and ineffective due to dualism in its diplomatic process, which involves collective negotiations through ASEAN and at the same time, individually through the national government. This resulted in a multiplicity of agreements, leading to the low number of FTA utilisation by private sectors. Third, Indonesia’s continued use of ASEAN as a medium for FTA negotiations leads to the strengthening of foreign policy goals relative to economic ones, due to ASEAN’s internal characteristics which focuses more on political-security relations, rather than economic ones. Based on these observations, Indonesia needs to reposition its FTA diplomacy to find a better balance between its foreign policy and trade goals.